Estudo da capacidade imunomoduladora in vivo de células-tronco mesenquimais obtidas da matriz do cordão umbilical equino - Dias, Marianne Camargos [UNESP] (2015)
Mesenchymal stem cells (MSCs) have therapeutic potential regulating inflammation, preventing the formation of wounds and regenerating tissues. MSCs derived from fetal membranes are highlighted because they are easy to obtain, from tissues usually discarded and with great possibility of bank formation. This study evaluated the in vivo inflammatory response of the gluteus medius muscle to the inoculation of allogeneic MSCs derived from equine umbilical cord. MSCs were cultured and characterized by immunophenotyping and differentiation into mesodermal lineages, and next cryopreserved. After thawing and expansion of MSCs transplantation was performed on day 0 in the right and left middle gluteal muscle at two different regions in six healthy mares. Likewise, for the control group, an injection of Hank's-Balanced Solution was performed caudally to the regions where MSCs were transplanted. Muscle biopsies were performed 30 days before the transplantation of MSCs, 2 days and 7 days after transplantation. All biopsies and transplants were preceded by ultrasonographic examination, and blood samples retrieval for hematological parameters. The biopsies were be analyzed by histological techniques. The MSCs were well characterized, and possessed high clonogenicity causing no changes in the hematological parameters evaluated. Ultrasound examination was suggestive of inflammation 48 hours after transplantation in both groups, control (C) and treated (T). Histological evaluation found no differences between C and T groups in any of the time points studied. A discrete temporal inflammation were found between D30 and D2 (P <0.05) only in the T group, however no differences were found in D7. Thus, we conclude that the cellular therapy did not incited systemic inflammatory response to recipients, demonstrating, for the first time, that the allogeneic use of MSCs from equine umbilical cord are safety for use in horse ...